Faster computation of left-bounded shortest unique substrings - Aguiar, Larissa L. M.; Louza, Felipe A. (Algorithms for molecular biology, 2025)
Finding shortest unique substrings (SUS) is a fundamental problem in string processing with applications in bioinformatics. In this paper, we present an algorithm for solving a variant of the SUS problem, the left-bounded shortest unique substrings (LSUS). This variant is particularly important in applications such as PCR primer design. Our algorithm runs in O ( n ) time using 2 n memory words plus n bytes for an input string of length n . Experimental results with real and artificial datasets show that our algorithm is the fastest alternative in practice, being two times faster (on the average) than related works, while using a similar peak memory footprint.